Genetic ancestry proportion influences risk of adverse events from tuberculosis treatment in Brazil - Jacqueline A. Piekos; Gustavo Amorim; Felipe Ridolfi; Marcelo Cordeiro-Santos; Afrânio L. Kritski; Marina C. Figueiredo; Bruno B. Andrade; Adalberto R. Santos; David W. Haas; Timothy R. Sterling; Valeria C. Rolla; Digna R. Velez Edwards; et al. (Human Genetics, 2026)
Tuberculosis (TB) treatment is highly effective, but response to therapy varies by geography and population subgroups. We assessed differences in TB treatment response in a representative and heterogeneous Brazilian population. We estimated genetic ancestry according to major genetic ancestry groups (African, European, and Amerindian) in the Regional Prospective Observational Research in Tuberculosis (RePORT)-Brazil cohort using ADMIXTURE software. RePORT-Brazil is an observational prospective cohort study of individuals with newly-diagnosed, culture-confirmed, pulmonary TB. Outcomes attributed to TB treatment included Grade 2 or higher adverse drug reaction (ADR), Grade 3 or higher ADR, hepatic ADR, and failure/recurrence. Genetic ancestry proportions were evaluated as predictors in univariate and multivariable logistic regression models for each outcome, and in stratified models for each genetic ancestry group. There were 930 pulmonary TB patients included in this study. In multivariable models we observed a decreased risk of Grade 2 + ADR when African ancestry proportion increased by 10% (Odds Ratio [OR] 0.41, 95% Confidence Interval [CI] 0.20–0.85) and an increased risk for Grade 2 + ADR with increasing European genetic ancestry (OR 2.33, 95% CI 1.14–4.76). In secondary analyses evaluating the interaction of HIV and genetic ancestry, we observed a statistically significant interaction between HIV and African genetic ancestry, but significantly decreased risk for Grade 2 + ADR with increasing African ancestry proportion. There were no associations with Amerindian genetic ancestry or for other treatment outcomes. In this Brazilian TB cohort, increased toxicity risk was associated with decreased African and increased European ancestry proportion.

“Persistent ecological impacts related to West Nile virus revealed using community science and vector surveillance data” - Brock Geary; Adam C. Smith; Lisa Williams; Sean P. Murphy; Brandon P.M. Edwards; Nicole L. Michel; Timothy D. Meehan; Roderick B. Gagne (Biological Conservation, 2026)

Effects of feeding on dogs’ frustration-related behaviours during a laboratory-based scent detection task - Jade Fountain; Journie Yee; Susan J. Hazel; Todd J. McWhorter; Tyler McNutt; Timothy L. Edwards (Behavioural Processes, 2026)

The Sedimentary Geochemistry and Paleoenvironments Project Phase 2 data release: An open data resource for the study of Earth's environmental history - Úna C. Farrell; Hunter C. Olson; Maya O. Thompson; Michelle L. Abshire; Oyeleye O. Adeboye; Anne-Sofie C. Ahm; Lewis J. Alcott; Thomas J. Algeo; Ross P. Anderson; Arif H. Ansari; Lucas Pinto Heckert Bastos; Kohen W. Bauer; et al. (Chemical Geology, 2026)

Reflectance spectroscopy (200-4200 nm) of the red-sloped C2 carbonaceous chondrites MET 00432, Tagish Lake, Tarda, and WIS 91600 (“CT” grouplet) - Edward A. Cloutis; Devin L. Schrader; Daniel M. Applin; Tomoki Nakamura; Timothy D. Glotch; Takahiro Hiroi; Moe Matsuoka; Michael E. Zolensky; Joshua P. Emery; Kristi M. Peters (Icarus, 2026)

Informing spatial conservation prioritization with species’ traits - Liam A. Trethowan; Laura Jennings; Haerul Arifin; Renata Borosova; Gemma L. C. Bramley; Marie Briggs; Osanna Chu; Ruth P. Clark; Sally Dawson; Kiran L. Dhanjal‐Adams; Yance de Freitas; James Hartup; et al. (Conservation Biology, 2026)
New Guinea, the most botanically diverse island on the planet, is the location for one of the boldest conservation initiatives. The Manokwari Declaration aims to achieve 70% conservation designation for the Bird's Head Peninsula. This is 40% higher than the 2022 Global Biodiversity Framework target. However, there is a lack of species occurrence data to support evidence of where biodiversity can be best protected. To address this, we integrated plant trait data from taxonomic descriptions in species occurrence models that can inform conservation planning. Inclusion of traits improved the performance of co‐occurrence models of ∼800 plant species across the 100,000‐km 2 landscape. Traits generally improved model performance, but not all traits contributed equally (e.g., leaf size and red flower color most improved accuracy of occurrence prediction). Likewise, trait‐parameterized models tended to be most useful with rare species occurrence prediction, but this was inconsistent among traits. Under 70% protection, three‐quarters of the areas selected conserved trait diversity. Critically, trait diversity also increased the chances that areas at high risk of deforestation were selected as conservation priorities. Overall, we found that plant species’ traits, often key parameters of ecosystem function and resilience, improved spatial conservation planning.

Determinants of L-band backscatter in dry tropical ecosystems: Implications for biomass mapping - João M.B. Carreiras; Thomas Higginbottom; John L. Godlee; Sam Harrison; Lorena Benitez; Penelope J. Mograbi; Aurora Levesley; Karina Melgaço; David Milodowski; Georgia Pickavance; Geoff Wells; Edmar Almeida de Oliveira; et al. (Remote Sensing of Environment, 2026)

The Sedimentary geochemistry and paleoenvironments project phase 2 data release: An open data resource for the study of Earth's environmental history - Úna C. Farrell; Hunter C. Olson; Maya O. Thompson; Michelle L. Abshire; Oyeleye O. Adeboye; Anne-Sofie C. Ahm; Lewis J. Alcott; Thomas J. Algeo; Ross P. Anderson; Arif H. Ansari; Lucas Pinto Heckert Bastos; Kohen W. Bauer; et al. (Chemical Geology, 2026)

Dogs can detect carp (Cyprinus rubrofuscus) using lake water samples - Melissa A. Collins; Samuel Barclay; Clare Browne; Nicholas Ling; Grant W. Tempero; Ian Kusabs; Timothy L. Edwards (Journal for Nature Conservation, 2026)

Seascape diversity and configuration shape habitat selection across multiple coastal ecosystems - Jesse D. Mosman; Hayden P. Borland; Ashley J. Rummell; Christopher J. Henderson; Sam Allan; Alec Bannam; Stacy L. Bierwagen; Michael J. Bradley; Alex B. Carter; Daniela M. Ceccarelli; Robert Coles; Michael J. Emslie; et al. (Biological Conservation, 2026)

Invasive catfish detection with scent detection dogs - Renee Denby; Lauren Hopkins; Lauren Little; Grant W. Tempero; Clare Browne; Melissa Collins; Nicholas Ling; Timothy L. Edwards (Applied Animal Behaviour Science, 2026)

Monitoring Resilience in Coastal Systems: A Comprehensive Assessment - Emma Imen Turki; Elena Ojeda; Ernesto Tonatiuth Mendoza; Gabriela Medellín; Timothy D. Price; Edward Salameh; Xiao Hua Wang; Li Li; Gemma L. Franklin; Alec Torres-Freyermuth (Journal of Marine Science and Engineering, 2025)
This work, conducted within the framework of the international network CRESTE (Coastal Resilience Using Satellites), examines the role of resilience in monitoring coastal evolution across diverse environments in Europe (France, The Netherlands), America (Mexico), Asia (China), and Oceania (Australia). High-resolution morphological datasets, derived from in situ measurements and video monitoring systems, were analyzed for wave- and tide-dominated beaches influenced by both climatic drivers and anthropogenic pressures. Findings indicate that beach resilience is strongly linked to system resistance, which depends on the intensity of climate drivers, including storm frequency, and site-specific conditions related to the type of sediment and its availability, and the presence of anthropogenic activities including coastal structures (e.g., Normandy, Yucatán) and shoreface nourishments (Netherlands). In Batemans Bay (Australia) and Hangzhou Bay (China), assessing the resilience is particularly challenging due to the combined influence of multiple drivers, fluvial inputs, and urban development. Accurate monitoring of coastal resilience across timescales requires accounting for long-term morphological, ecological, and socio-economic processes. This can be enhanced through satellite observations, which, when integrated with in situ measurements, numerical modeling, and artificial intelligence, support a more comprehensive assessment of resilience and refine projections under future climate change and sea-level rise; representing a key focus for further works.

Network of networks: Time series clustering of AmeriFlux sites - David E Reed; Housen Chu; Brad G. Peter; Jiquan Chen; Michael Abraha; Brian Amiro; Ray G. Anderson; M. Altaf Arain; Paulo Arruda; Greg A. Barron-Gafford; Carl Bernacchi; Daniel P. Beverly; et al. (Agricultural and Forest Meteorology, 2025)

Biogeochemical controls on iron speciation and cycling across upland to shoreline gradients in freshwater and estuarine coastal soils (Lake Erie and Chesapeake Bay, United States) - Lucie Stetten; Maxim I. Boyanov; Edward J. O'Loughlin; Shan Pushpajom Thomas; Kathleen R. Beilsmith; Roberta B. Peixoto; Fausto Machado-Silva; Donnie J. Day; Stephanie J. Wilson; Timothy W. Vugteveen; Allison N. Myers-Pigg; Opal Otenburg; et al. (Science of The Total Environment, 2025)

Variety-seeking behavioral markers in an immersive virtual reality food buffet are associated with greater food and energy intake in laboratory meals - John W. Long; Paige M. Cunningham; Sara J. Maksi; Kathleen L. Keller; Charissa S.L. Cheah; Lee Boot; Alexander Klippel; Timothy R. Brick; Caitlyn G. Edwards; Janelle Kort; Paige Grabusky; Barbara J. Rolls; et al. (Appetite, 2025)

BioTIME 2.0: Expanding and Improving a Database of Biodiversity Time Series - Maria Dornelas; Laura H. Antão; Amanda E. Bates; Viviana Brambilla; Jonathan M. Chase; Cher F. Y. Chow; Ada Fontrodona‐Eslava; Anne E. Magurran; Inês S. Martins; Faye Moyes; Alban Sagouis; Samuel Adu‐Acheampong; et al. (Global Ecology and Biogeography, 2025)
Motivation Here, we make available a second version of the BioTIME database, which compiles records of abundance estimates for species in sample events of ecological assemblages through time. The updated version expands version 1.0 of the database by doubling the number of studies and includes substantial additional curation to the taxonomic accuracy of the records, as well as the metadata. Moreover, we now provide an R package (BioTIMEr) to facilitate use of the database. Main Types of Variables Included The database is composed of one main data table containing the abundance records and 11 metadata tables. The data are organised in a hierarchy of scales where 11,989,233 records are nested in 1,603,067 sample events, from 553,253 sampling locations, which are nested in 708 studies. A study is defined as a sampling methodology applied to an assemblage for a minimum of 2 years. Spatial Location and Grain Sampling locations in BioTIME are distributed across the planet, including marine, terrestrial and freshwater realms. Spatial grain size and extent vary across studies depending on sampling methodology. We recommend gridding of sampling locations into areas of consistent size. Time Period and Grain The earliest time series in BioTIME start in 1874, and the most recent records are from 2023. Temporal grain and duration vary across studies. We recommend doing sample‐level rarefaction to ensure consistent sampling effort through time before calculating any diversity metric. Major Taxa and Level of Measurement The database includes any eukaryotic taxa, with a combined total of 56,400 taxa. Software Format csv and. SQL.

Dietary Fiber Intake and Risk of Advanced and Aggressive Forms of Prostate Cancer: A Pooled Analysis of 15 Prospective Cohort Studies - Elkhansa Sidahmed; Stephen J. Freedland; Molin Wang; Kana Wu; Demetrius Albanes; Matt Barnett; Piet A. van den Brandt; Michael B. Cook; Graham G. Giles; Edward Giovannucci; Christopher A. Haiman; Susanna C. Larsson; et al. (Journal of the Academy of Nutrition and Dietetics, 2025)

Carbon recovery in secondary forests: Insights from three West African countries - Paly N. Titenwi; Moses N. Sainge; Usif Kargbo; Richard A.S. Kamara; Alex Musa; Timothy M. Kabba; Bockarie K. Buanie; Andre L. Njouonkou; Edward Aruna; Martin J.P. Sullivan; Ana Leite; Aida Cuni-Sanchez (Forest Ecology and Management, 2025)

The Toxicology Investigators Consortium 2023 Annual Report - Adrienne Hughes; Alexandra Amaducci; Sharan L. Campleman; Shao Li; Mari Costantini; Meghan B. Spyres; Hannah Spungen; Jessica Kent; Alyssa Falise; Rachel Culbreth; Paul M. Wax; Jeffery Brent; et al. (Journal of Medical Toxicology, 2024)

Damage to tropical forests caused by cyclones is driven by wind speed but mediated by topographical exposure and tree characteristics - Thomas Ibanez; David Bauman; Shin‐ichiro Aiba; Thomas Arsouze; Peter J. Bellingham; Chris Birkinshaw; Philippe Birnbaum; Timothy J. Curran; Saara J. DeWalt; John Dwyer; Thierry Fourcaud; Janet Franklin; et al. (Global Change Biology, 2024)
Each year, an average of 45 tropical cyclones affect coastal areas and potentially impact forests. The proportion of the most intense cyclones has increased over the past four decades and is predicted to continue to do so. Yet, it remains uncertain how topographical exposure and tree characteristics can mediate the damage caused by increasing wind speed. Here, we compiled empirical data on the damage caused by 11 cyclones occurring over the past 40 years, from 74 forest plots representing tropical regions worldwide, encompassing field data for 22,176 trees and 815 species. We reconstructed the wind structure of those tropical cyclones to estimate the maximum sustained wind speed (MSW) and wind direction at the studied plots. Then, we used a causal inference framework combined with Bayesian generalised linear mixed models to understand and quantify the causal effects of MSW, topographical exposure to wind (EXP), tree size (DBH) and species wood density ( ρ ) on the proportion of damaged trees at the community level, and on the probability of snapping or uprooting at the tree level. The probability of snapping or uprooting at the tree level and, hence, the proportion of damaged trees at the community level, increased with increasing MSW, and with increasing EXP accentuating the damaging effects of cyclones, in particular at higher wind speeds. Higher ρ decreased the probability of snapping and to a lesser extent of uprooting. Larger trees tended to have lower probabilities of snapping but increased probabilities of uprooting. Importantly, the effect of ρ decreasing the probabilities of snapping was more marked for smaller than larger trees and was further accentuated at higher MSW. Our work emphasises how local topography, tree size and species wood density together mediate cyclone damage to tropical forests, facilitating better predictions of the impacts of such disturbances in an increasingly windier world.

Effects of sample preservation techniques on dogs' (Canis familiaris) ability to detect koi carp (Cyprinus rubrofuscus) - Melissa A. Collins; Clare M. Browne; Timothy L. Edwards; Nicholas Ling; Grant W. Tempero (Applied Animal Behaviour Science, 2024)

State of the California Current Ecosystem report in 2022: a tale of two La Niñas - Andrew R. Thompson; Rasmus Swalethorp; Michaela Alksne; Jarrod A. Santora; Elliott L. Hazen; Andrew Leising; Erin Satterthwaite; William J. Sydeman; Clarissa R. Anderson; Toby D. Auth; Simone Baumann-Pickering; Timothy Baumgardner; et al. (Frontiers in Marine Science, 2024)
2022 marked the third consecutive La Niña and extended the longest consecutive stretch of negative Oceanic Niño Index since 1998-2001. While physical and biological conditions in winter and spring largely adhered to prior La Niña conditions, summer and fall were very different. Similar to past La Niña events, in winter and spring coastal upwelling was either average or above average, temperature average or below average, salinity generally above average. In summer and fall, however, upwelling and temperature were generally average or slightly below average, salinity was close to average and chlorophyll a was close to average. Again, as during prior La Niña events, biomass of northern/southern copepods was above/below average off Oregon in winter, and body size of North Pacific krill in northern California was above average in winter. By contrast, later in the year the abundance of northern krill dropped off Oregon while southern copepods increased and body sizes of North Pacific krill fell in northern California. Off Oregon and Washington abundances of market squid and Pacific pompano (indicators of warm, non-typical La Niña conditions) were high. In the 20 th century, Northern anchovy recruitment tended to be high during cold conditions, but despite mostly warm conditions from 2015-2021 anchovy populations boomed and remained high in 2022. Resident seabird reproductive success, which tended in the past to increase during productive La Niña conditions was highly variable throughout the system as common murre and pelagic cormorant, experienced complete reproductive failure at Yaquina Head, Oregon while Brandt’s cormorant reproduction was average. At three sampling locations off central California, however, common murre reproduction was close to or above average while both pelagic and Brandt’s cormorant were above average. California sealion reproduction has been above average each year since 2016, and pup weight was also above average in 2022, likely in response not to La Niña or El Niño but continuous high abundance of anchovy. The highly variable and often unpredictable physical and biological conditions in 2022 highlight a growing recognition of disconnects between basin-scale indices and local conditions in the CCE. “July-December 2022 is the biggest outlier from individual “strong” La Niña (events) ever going back to the 50s.” – Nate Mantua

Portion size affects food selection in an immersive virtual reality buffet and is related to measured intake in laboratory meals varying in portion size - John W. Long; Sara J. Pritschet; Kathleen L. Keller; Charissa S.L. Cheah; Lee Boot; Alexander Klippel; Timothy R. Brick; Caitlyn G. Edwards; Barbara J. Rolls; Travis D. Masterson (Appetite, 2023)

Extracting spatial information from temporal odor patterns: insights from insects - Paul Szyszka; Thierry Emonet; Timothy L Edwards (Current Opinion in Insect Science, 2023)

The Toxicology Investigators Consortium 2022 Annual Report - Alexandra M. Amaducci; Sharan L. Campleman; Shao Li; Dana L. Karshenas; Meghan B. Spyres; Lynn A. Farrugia; A. Min Kang; Rachel E. Culbreth; Paul M. Wax; Jeffrey Brent; Kim Aldy; Jennifer Acciani; et al. (Journal of Medical Toxicology, 2023)

The Toxicology Investigators Consortium Case Registry—the 2021 Annual Report - Jennifer S. Love; Dana L. Karshenas; Meghan B. Spyres; Lynn A. Farrugia; A. Min Kang; HoanVu Nguyen; Sharan L. Campleman; Shao Li; Paul M. Wax; Jeffery Brent; Kim Aldy; Michael Abesamis; et al. (Journal of Medical Toxicology, 2022)

Corrigendum: State of the California Current 2019–2020: Back to the Future With Marine Heatwaves? - Edward D. Weber; Toby D. Auth; Simone Baumann-Pickering; Timothy R. Baumgartner; Eric P. Bjorkstedt; Steven J. Bograd; Brian J. Burke; José L. Cadena-Ramírez; Elizabeth A. Daly; Martin de la Cruz; Heidi Dewar; John C. Field; et al. (Frontiers in Marine Science, 2022)

Genetic analyses of gynecological disease identify genetic relationships between uterine fibroids and endometrial cancer, and a novel endometrial cancer genetic risk region at the WNT4 1p36.12 locus - Pik Fang Kho; Sally Mortlock; Frederic Amant; Daniela Annibali; Katie Ashton; John Attia; Paul L. Auer; Matthias W. Beckmann; Amanda Black; Louise Brinton; Daniel D. Buchanan; Stephen J. Chanock; et al. (Human Genetics, 2021)

State of the California Current 2019–2020: Back to the Future With Marine Heatwaves? - Edward D. Weber; Toby D. Auth; Simone Baumann-Pickering; Timothy R. Baumgartner; Eric P. Bjorkstedt; Steven J. Bograd; Brian J. Burke; José L. Cadena-Ramírez; Elizabeth A. Daly; Martin de la Cruz; Heidi Dewar; John C. Field; et al. (Frontiers in Marine Science, 2021)
The California Current System (CCS) has experienced large fluctuations in environmental conditions in recent years that have dramatically affected the biological community. Here we synthesize remotely sensed, hydrographic, and biological survey data from throughout the CCS in 2019–2020 to evaluate how recent changes in environmental conditions have affected community dynamics at multiple trophic levels. A marine heatwave formed in the north Pacific in 2019 and reached the second greatest area ever recorded by the end of summer 2020. However, high atmospheric pressure in early 2020 drove relatively strong Ekman-driven coastal upwelling in the northern portion of the CCS and warm temperature anomalies remained far offshore. Upwelling and cooler temperatures in the northern CCS created relatively productive conditions in which the biomass of lipid-rich copepod species increased, adult krill size increased, and several seabird species experienced positive reproductive success. Despite these conditions, the composition of the fish community in the northern CCS remained a mixture of both warm- and cool-water-associated species. In the southern CCS, ocean temperatures remained above average for the seventh consecutive year. Abundances of juvenile fish species associated with productive conditions were relatively low, and the ichthyoplankton community was dominated by a mixture of oceanic warm-water and cosmopolitan species. Seabird species associated with warm water also occurred at greater densities than cool-water species in the southern CCS. The population of northern anchovy, which has been resurgent since 2017, continued to provide an important forage base for piscivorous fishes, offshore colonies of seabirds, and marine mammals throughout the CCS. Coastal upwelling in the north, and a longer-term trend in warming in the south, appeared to be controlling the community to a much greater extent than the marine heatwave itself.

Developmental Timeline of Wild Aye-Aye (Daubentonia madagascariensis) Infants in Kianjavato and Torotorofotsy, Madagascar - Jeannin Nicolas Rakotondrazandry; Faranky Ravelomandrato; Timothy M. Sefczek; Yves Rostant Andriamalala; Cynthia L. Frasier; Vicki L. Villanova; Solofonirina Rasoloharijaona; Herimalala Raveloson; Edward E. Louis (International Journal of Primatology, 2021)

Pantropical variability in tree crown allometry - Grace Jopaul Loubota Panzou; Adeline Fayolle; Tommaso Jucker; Oliver L. Phillips; Stephanie Bohlman; Lindsay F. Banin; Simon L. Lewis; Kofi Affum‐Baffoe; Luciana F. Alves; Cécile Antin; Eric Arets; Luzmila Arroyo; et al. (Global Ecology and Biogeography, 2021)
Aim Tree crowns determine light interception, carbon and water exchange. Thus, understanding the factors causing tree crown allometry to vary at the tree and stand level matters greatly for the development of future vegetation modelling and for the calibration of remote sensing products. Nevertheless, we know little about large‐scale variation and determinants in tropical tree crown allometry. In this study, we explored the continental variation in scaling exponents of site‐specific crown allometry and assessed their relationships with environmental and stand‐level variables in the tropics. Location Global tropics. Time period Early 21st century. Major taxa studied Woody plants. Methods Using a dataset of 87,737 trees distributed among 245 forest and savanna sites across the tropics, we fitted site‐specific allometric relationships between crown dimensions (crown depth, diameter and volume) and stem diameter using power‐law models. Stand‐level and environmental drivers of crown allometric relationships were assessed at pantropical and continental scales. Results The scaling exponents of allometric relationships between stem diameter and crown dimensions were higher in savannas than in forests. We identified that continental crown models were better than pantropical crown models and that continental differences in crown allometric relationships were driven by both stand‐level (wood density) and environmental (precipitation, cation exchange capacity and soil texture) variables for both tropical biomes. For a given diameter, forest trees from Asia and savanna trees from Australia had smaller crown dimensions than trees in Africa and America, with crown volumes for some Asian forest trees being smaller than those of trees in African forests. Main conclusions Our results provide new insight into geographical variability, with large continental differences in tropical tree crown allometry that were driven by stand‐level and environmental variables. They have implications for the assessment of ecosystem function and for the monitoring of woody biomass by remote sensing techniques in the global tropics.

Climate change literature and information gaps in mountainous headwaters of the Columbia River Basin - Adrienne M. Marshall; Meghan Foard; Courtney M. Cooper; Paris Edwards; Shana L. Hirsch; Micah Russell; Timothy E. Link (Regional Environmental Change, 2020)

The global abundance of tree palms - Robert Muscarella; Thaise Emilio; Oliver L. Phillips; Simon L. Lewis; Ferry Slik; William J. Baker; Thomas L. P. Couvreur; Wolf L. Eiserhardt; Jens‐Christian Svenning; Kofi Affum‐Baffoe; Shin‐Ichiro Aiba; Everton C. de Almeida; et al. (Global Ecology and Biogeography, 2020)
Aim Palms are an iconic, diverse and often abundant component of tropical ecosystems that provide many ecosystem services. Being monocots, tree palms are evolutionarily, morphologically and physiologically distinct from other trees, and these differences have important consequences for ecosystem services (e.g., carbon sequestration and storage) and in terms of responses to climate change. We quantified global patterns of tree palm relative abundance to help improve understanding of tropical forests and reduce uncertainty about these ecosystems under climate change. Location Tropical and subtropical moist forests. Time period Current. Major taxa studied Palms (Arecaceae). Methods We assembled a pantropical dataset of 2,548 forest plots (covering 1,191 ha) and quantified tree palm (i.e., ≥10 cm diameter at breast height) abundance relative to co‐occurring non‐palm trees. We compared the relative abundance of tree palms across biogeographical realms and tested for associations with palaeoclimate stability, current climate, edaphic conditions and metrics of forest structure. Results On average, the relative abundance of tree palms was more than five times larger between Neotropical locations and other biogeographical realms. Tree palms were absent in most locations outside the Neotropics but present in >80% of Neotropical locations. The relative abundance of tree palms was more strongly associated with local conditions (e.g., higher mean annual precipitation, lower soil fertility, shallower water table and lower plot mean wood density) than metrics of long‐term climate stability. Life‐form diversity also influenced the patterns; palm assemblages outside the Neotropics comprise many non‐tree (e.g., climbing) palms. Finally, we show that tree palms can influence estimates of above‐ground biomass, but the magnitude and direction of the effect require additional work. Conclusions Tree palms are not only quintessentially tropical, but they are also overwhelmingly Neotropical. Future work to understand the contributions of tree palms to biomass estimates and carbon cycling will be particularly crucial in Neotropical forests.

BioTIME: A database of biodiversity time series for the Anthropocene - Maria Dornelas; Laura H. Antão; Faye Moyes; Amanda E. Bates; Anne E. Magurran; Dušan Adam; Asem A. Akhmetzhanova; Ward Appeltans; José Manuel Arcos; Haley Arnold; Narayanan Ayyappan; Gal Badihi; et al. (Global Ecology and Biogeography, 2018)
Motivation The BioTIME database contains raw data on species identities and abundances in ecological assemblages through time. These data enable users to calculate temporal trends in biodiversity within and amongst assemblages using a broad range of metrics. BioTIME is being developed as a community‐led open‐source database of biodiversity time series. Our goal is to accelerate and facilitate quantitative analysis of temporal patterns of biodiversity in the Anthropocene. Main types of variables included The database contains 8,777,413 species abundance records, from assemblages consistently sampled for a minimum of 2 years, which need not necessarily be consecutive. In addition, the database contains metadata relating to sampling methodology and contextual information about each record. Spatial location and grain BioTIME is a global database of 547,161 unique sampling locations spanning the marine, freshwater and terrestrial realms. Grain size varies across datasets from 0.0000000158 km 2 (158 cm 2 ) to 100 km 2 (1,000,000,000,000 cm 2 ). Time period and grain BioTIME records span from 1874 to 2016. The minimal temporal grain across all datasets in BioTIME is a year. Major taxa and level of measurement BioTIME includes data from 44,440 species across the plant and animal kingdoms, ranging from plants, plankton and terrestrial invertebrates to small and large vertebrates. Software format .csv and .SQL.

Ecosystem state shifts during long‐term development of an Amazonian peatland - Graeme T. Swindles; Paul J. Morris; Bronwen Whitney; Jennifer M. Galloway; Mariusz Gałka; Angela Gallego‐Sala; Andrew L. Macumber; Donal Mullan; Mark W. Smith; Matthew J. Amesbury; Thomas P. Roland; Hamed Sanei; et al. (Global Change Biology, 2018)
The most carbon (C)‐dense ecosystems of Amazonia are areas characterized by the presence of peatlands. However, Amazonian peatland ecosystems are poorly understood and are threatened by human activities. Here, we present an investigation into long‐term ecohydrological controls on C accumulation in an Amazonian peat dome. This site is the oldest peatland yet discovered in Amazonia (peat initiation ca. 8.9 ka BP ), and developed in three stages: (i) peat initiated in an abandoned river channel with open water and aquatic plants; (ii) inundated forest swamp; and (iii) raised peat dome (since ca. 3.9 ka BP ). Local burning occurred at least three times in the past 4,500 years. Two phases of particularly rapid C accumulation (ca. 6.6–6.1 and ca. 4.9–3.9 ka BP ), potentially resulting from increased net primary productivity, were seemingly driven by drier conditions associated with widespread drought events. The association of drought phases with major ecosystem state shifts (open water wetland–forest swamp–peat dome) suggests a potential climatic control on the developmental trajectory of this tropical peatland. A third drought phase centred on ca. 1.8–1.1 ka BP led to markedly reduced C accumulation and potentially a hiatus during the peat dome stage. Our results suggest that future droughts may lead to phases of rapid C accumulation in some inundated tropical peat swamps, although this can lead ultimately to a shift to ombrotrophy and a subsequent return to slower C accumulation. Conversely, in ombrotrophic peat domes, droughts may lead to reduced C accumulation or even net loss of peat. Increased surface wetness at our site in recent decades may reflect a shift towards a wetter climate in western Amazonia. Amazonian peatlands represent important carbon stores and habitats, and are important archives of past climatic and ecological information. They should form key foci for conservation efforts.

Music as an Adjunct to Opioid-Based Analgesia - Peter R. Chai; Stephanie Carreiro; Megan L. Ranney; Ketki Karanam; Marko Ahtisaari; Robert Edwards; Kristin L. Schreiber; Lubabah Ben-Ghaly; Timothy B. Erickson; Edward W. Boyer (Journal of Medical Toxicology, 2017)

Gene loss in the fungal canola pathogen Leptosphaeria maculans - Agnieszka A. Golicz; Paula A. Martinez; Manuel Zander; Dhwani A. Patel; Angela P. Van De Wouw; Paul Visendi; Timothy L. Fitzgerald; David Edwards; Jacqueline Batley (Functional & Integrative Genomics, 2015)

Markedly divergent estimates of A mazon forest carbon density from ground plots and satellites - Edward T. A. Mitchard; Ted R. Feldpausch; Roel J. W. Brienen; Gabriela Lopez‐Gonzalez; Abel Monteagudo; Timothy R. Baker; Simon L. Lewis; Jon Lloyd; Carlos A. Quesada; Manuel Gloor; Hans ter Steege; Patrick Meir; et al. (Global Ecology and Biogeography, 2014)
Aim The accurate mapping of forest carbon stocks is essential for understanding the global carbon cycle, for assessing emissions from deforestation, and for rational land‐use planning. Remote sensing ( RS ) is currently the key tool for this purpose, but RS does not estimate vegetation biomass directly, and thus may miss significant spatial variations in forest structure. We test the stated accuracy of pantropical carbon maps using a large independent field dataset. Location Tropical forests of the A mazon basin. The permanent archive of the field plot data can be accessed at: http://dx.doi.org/10.5521/FORESTPLOTS.NET/2014_1 Methods Two recent pantropical RS maps of vegetation carbon are compared to a unique ground‐plot dataset, involving tree measurements in 413 large inventory plots located in nine countries. The RS maps were compared directly to field plots, and kriging of the field data was used to allow area‐based comparisons. Results The two RS carbon maps fail to capture the main gradient in Amazon forest carbon detected using 413 ground plots, from the densely wooded tall forests of the north‐east, to the light‐wooded, shorter forests of the south‐west. The differences between plots and RS maps far exceed the uncertainties given in these studies, with whole regions over‐ or under‐estimated by > 25%, whereas regional uncertainties for the maps were reported to be Main conclusions Pantropical biomass maps are widely used by governments and by projects aiming to reduce deforestation using carbon offsets, but may have significant regional biases. Carbon‐mapping techniques must be revised to account for the known ecological variation in tree wood density and allometry to create maps suitable for carbon accounting. The use of single relationships between tree canopy height and above‐ground biomass inevitably yields large, spatially correlated errors. This presents a significant challenge to both the forest conservation and remote sensing communities, because neither wood density nor species assemblages can be reliably mapped from space.

The global contribution of forage fish to marine fisheries and ecosystems - Ellen K Pikitch; Konstantine J Rountos; Timothy E Essington; Christine Santora; Daniel Pauly; Reg Watson; Ussif R Sumaila; P Dee Boersma; Ian L Boyd; David O Conover; Philippe Cury; Selina S Heppell; et al. (Fish and Fisheries, 2014)
Forage fish play a pivotal role in marine ecosystems and economies worldwide by sustaining many predators and fisheries directly and indirectly. We estimate global forage fish contributions to marine ecosystems through a synthesis of 72 published E copath models from around the world. Three distinct contributions of forage fish were examined: (i) the ecological support service of forage fish to predators in marine ecosystems, (ii) the total catch and value of forage fisheries and (iii) the support service of forage fish to the catch and value of other commercially targeted predators. Forage fish use and value varied and exhibited patterns across latitudes and ecosystem types. Forage fish supported many kinds of predators, including fish, seabirds, marine mammals and squid. Overall, forage fish contribute a total of about $16.9 billion USD to global fisheries values annually, i.e. 20% of the global ex‐vessel catch values of all marine fisheries combined. While the global catch value of forage fisheries was $5.6 billion, fisheries supported by forage fish were more than twice as valuable ($11.3 billion). These estimates provide important information for evaluating the trade‐offs of various uses of forage fish across ecosystem types, latitudes and globally. We did not estimate a monetary value for supportive contributions of forage fish to recreational fisheries or to uses unrelated to fisheries, and thus the estimates of economic value reported herein understate the global value of forage fishes.

Priority research questions for the UK food system - John S. I. Ingram; Hugh L. Wright; Lucy Foster; Timothy Aldred; David Barling; Tim G. Benton; Paul M. Berryman; Charles S. Bestwick; Alice Bows-Larkin; Tim F. Brocklehurst; Judith Buttriss; John Casey; et al. (Food Security, 2013)
The rise of food security up international political, societal and academic agendas has led to increasing interest in novel means of improving primary food production and reducing waste. There are however, also many ‘post-farm gate’ activities that are critical to food security, including processing, packaging, distributing, retailing, cooking and consuming. These activities all affect a range of important food security elements, notably availability, affordability and other aspects of access, nutrition and safety. Addressing the challenge of universal food security, in the context of a number of other policy goals (e.g. social, economic and environmental sustainability), is of keen interest to a range of UK stakeholders but requires an up-to-date evidence base and continuous innovation. An exercise was therefore conducted, under the auspices of the UK Global Food Security Programme, to identify priority research questions with a focus on the UK food system (though the outcomes may be broadly applicable to other developed nations). Emphasis was placed on incorporating a wide range of perspectives (‘world views’) from different stakeholder groups: policy, private sector, non-governmental organisations, advocacy groups and academia. A total of 456 individuals submitted 820 questions from which 100 were selected by a process of online voting and a three-stage workshop voting exercise. These 100 final questions were sorted into 10 themes and the ‘top’ question for each theme identified by a further voting exercise. This step also allowed four different stakeholder groups to select the top 7–8 questions from their perspectives. Results of these voting exercises are presented. It is clear from the wide range of questions prioritised in this exercise that the different stakeholder groups identified specific research needs on a range of post-farm gate activities and food security outcomes. Evidence needs related to food affordability, nutrition and food safety (all key elements of food security) featured highly in the exercise. While there were some questions relating to climate impacts on production, other important topics for food security (e.g. trade, transport, preference and cultural needs) were not viewed as strongly by the participants.

No evidence for cumulative effects in a Dnmt3b hypomorph across multiple generations - Neil A. Youngson; Trevor Epp; Amity R. Roberts; Lucia Daxinger; Alyson Ashe; Edward Huang; Krystal L. Lester; Sarah K. Harten; Graham F. Kay; Timothy Cox; Jacqueline M. Matthews; Suyinn Chong; et al. (Mammalian Genome, 2013)

Genetic variation of single nucleotide polymorphisms identified at the mating type locus correlates with form-specific disease phenotype in the barley net blotch fungus Pyrenophora teres - Shunwen Lu; Michael C. Edwards; Timothy L. Friesen (European Journal of Plant Pathology, 2013)

Application of large-scale sequencing to marker discovery in plants - Robert J Henry; Mark Edwards; Daniel L E Waters; Gopala Krishnan S; Peter Bundock; Timothy R Sexton; Ardashir K Masouleh; Catherine J Nock; Julie Pattemore (Journal of Biosciences, 2012)

Comparative genomics reveals functional transcriptional control sequences in the Prop1 gene - Robert D. Ward; Shannon W. Davis; MinChul Cho; Constance Esposito; Robert H. Lyons; Jan-Fang Cheng; Edward M. Rubin; Simon J. Rhodes; Lori T. Raetzman; Timothy P. L. Smith; Sally A. Camper (Mammalian Genome, 2007)

Molecular and Physiological Differentiation Between Pathogenic and Nonpathogenic Acanthamoeba - Naveed A. Khan; Edward L. Jarroll; Timothy A. Paget (Current Microbiology, 2002)

Acanthamoeba Can Be Differentiated by the Polymerase Chain Reaction and Simple Plating Assays - Naveed A. Khan; Edward L. Jarroll; Timothy A. Paget (Current Microbiology, 2001)

Intact negative patterning in rats with fornix or combined perirhinal and postrhinal cortex lesions - Timothy J. Bussey; Rebecca Dias; Edward S. Redhead; John M. Pearce; Janice L. Muir; John P. Aggleton (Experimental Brain Research, 2000)